A Case Report of a Rare Huge Ureteral Fibroepithelial Polyp: Challenges and Clinical Management - Alireza Akhavan Rezayat; Amir Yarahmadi; Atena Aghaee; Farid Zeynali; Salman Soltani (Case Reports in Clinical Practice, 2022)
Ureteral fibroepithelial polyps (UFPs) are rare abnormality that may cause ureteral obstruction. Herein, we report a 35- year- old woman with flank pain, dysuria, frequency and transient total gross hematuria. A mass in the right ureter was reported on imaging and in endoscopic evaluation, small polypoid mass protruding from the right ureteral orifice in the bladder, and a huge ureteral mass originating from proximal ureter was observed. A right subcostal flank incision was done, a huge polypoid mass with a segment of ureteral was excised, and end-to-end anastomosis of the ureter was done. Histopathological examination showed a UFP without malignancy.